Reflections on the jurisprudential treatment of managers and trusted personnel - Toyama Miyagusuku, Jorge (2014)
In labor relations, there are workers who, because of the role they play in the managementof a corporation or the privileged information they handle, receive a special treatment from Labor Law: Direction and reliable workers.Because of their particular situation, many questions may arise regarding the legal treatment and labor benefits that these workers may hold. In the present article, the authors try to answer to these questions, in the light of the jurisprudence of the Peruvian Supreme Court and our country’s Constitutional Court.